2013
DOI: 10.1038/ncomms3775
|View full text |Cite
|
Sign up to set email alerts
|

Doped organic transistors operating in the inversion and depletion regime

Abstract: The inversion field-effect transistor is the basic device of modern microelectronics and is nowadays used more than a billion times on every state-of-the-art computer chip. In the future, this rigid technology will be complemented by flexible electronics produced at extremely low cost. Organic field-effect transistors have the potential to be the basic device for flexible electronics, but still need much improvement. In particular, despite more than 20 years of research, organic inversion mode transistors have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
192
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 177 publications
(197 citation statements)
references
References 25 publications
5
192
0
Order By: Relevance
“…[13] In this early work, the molecule was used to p-dope N,N′-di-1-naphthyl-N,N′-diphenyl-1,1′-biphenyl-4,4′diamine (α-NPD, IE ≈ 5.5 eV) and shown to significantly increase the current density sustained by these films. It was then introduced by Tietze et al [14] and Lüssem et al [15] in electronic structure and device investigations, and found to efficiently p-dope MeO-TPD or pentacene (IE ≈ 4.95 eV). Yet, the EA of the dopant and its doping limit were not fully established.…”
mentioning
confidence: 99%
“…[13] In this early work, the molecule was used to p-dope N,N′-di-1-naphthyl-N,N′-diphenyl-1,1′-biphenyl-4,4′diamine (α-NPD, IE ≈ 5.5 eV) and shown to significantly increase the current density sustained by these films. It was then introduced by Tietze et al [14] and Lüssem et al [15] in electronic structure and device investigations, and found to efficiently p-dope MeO-TPD or pentacene (IE ≈ 4.95 eV). Yet, the EA of the dopant and its doping limit were not fully established.…”
mentioning
confidence: 99%
“…This linear dependence of the threshold voltage shift upon the thickness of the doped channel proves that the shift of the threshold voltage is due to real doping and thus generation of free charge carriers in the channel region. 6 In contrast to the depletion transistors presented in Fig. 2, top-gate organic inversion transistors have not been realized before.…”
Section: Top-gate Organic Depletion and Inversion Transistors With Domentioning
confidence: 99%
“…10,17 L€ ussem et al have previously investigated the Fermi level shift upon doping by ultraviolet photoelectron spectroscopy (UPS) in order to distinguish between the trap filling by doping and the increase of free charge carriers in the bulk of pentacene. 6 They found that the Fermi level shifts significantly towards the transport states, which proves that doping can greatly increase the charge carrier density in the channel region. However, to fully prove that a trap filling at the pentacene/Cytop interface has a negligible effect on the threshold voltage, we study the dependence of the shift of threshold voltage on the thickness of the doped channel.…”
Section: Top-gate Organic Depletion and Inversion Transistors With Domentioning
confidence: 99%
See 2 more Smart Citations